2007
DOI: 10.1152/ajpheart.01301.2006
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific and exercise-acquired cardioprotection is abolished by sarcolemmal KATP channel blockade in the rat heart

Abstract: Chicco AJ, Johnson MS, Armstrong CJ, Lynch JM, Gardner RT, Fasen GS, Gillenwater CP, Moore RL. Sex-specific and exercise-acquired cardioprotection is abolished by sarcolemmal KATP channel blockade in the rat heart. Am J Physiol Heart Circ Physiol 292: H2432-H2437, 2007. First published January 19, 2007; doi:10.1152/ajpheart.01301.2006.-The present study was conducted to determine whether the infarct sparing effect of shortterm exercise is dependent on the operation of the myocardial sarcolemmal ATP-sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
50
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 60 publications
3
50
0
1
Order By: Relevance
“…Collectively, previous and present findings may indicate the sarc K ATP channel mediates tissue preservation during IR, while the mito K ATP channel protects against arrhythmias (20). The protective contribution of the mito and sarc K ATP channels does not, however, appear to be consistent across all experimental paradigms and requires further investigation (12)(13)17). Accordingly, we employed a relatively short-duration ischemia (20 min) and proportionate reperfusion period (30 min) to evaluate the impact of these ion channels as potential mechanisms of anti-arrhythmic protection in the exercised heart and investigated biochemical outcomes in perfused and ischemic myocardium before the overt onset of tissue death occurred.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Collectively, previous and present findings may indicate the sarc K ATP channel mediates tissue preservation during IR, while the mito K ATP channel protects against arrhythmias (20). The protective contribution of the mito and sarc K ATP channels does not, however, appear to be consistent across all experimental paradigms and requires further investigation (12)(13)17). Accordingly, we employed a relatively short-duration ischemia (20 min) and proportionate reperfusion period (30 min) to evaluate the impact of these ion channels as potential mechanisms of anti-arrhythmic protection in the exercised heart and investigated biochemical outcomes in perfused and ischemic myocardium before the overt onset of tissue death occurred.…”
Section: Discussionmentioning
confidence: 60%
“…37). Characteristic of experimentation with pharmacological inhibitors, however, we cannot rule out the possibility of unknown pharmacological effects in the present study, including 5HD-specific effects on substrate availability (5,26) and sex specific effects (17). Despite the potential role of 5HD metabolism within the heart, the resulting implications for outcomes related to preconditioning remain unknown.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Pollesellop et al [10] have shown that levosimendan has [10] vasodilatory and anti ischemic effects mediated via the opening of ATP-sensitive K channels in vascular smooth-muscle cells and also acts on mitochondrial ATPsensitive K (mito KATP) channels, an action thought to protect the heart against IR damage. Chicco et al abolished [11] the sarcolemmal K (ATP) channel blockade training-induced cardio protection increasing infarct size to 47.5±3.5% of zone at risk (ZAR) in rats. This study demonstrates that resistance to myocardial IR injury is dependent on sarcolemmal K (ATP) activity during ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…While women are known to exhibit reduced risk of cardiovascular events and associated mortality compared to males, the molecular mechanisms of this sex-dimorphism remains incompletely understood [9][10][11]. Animal studies have demonstrated an intrinsic resistance of the female heart to ischemia/ reperfusion injury, which has been linked to a higher expression of sarcK ATP channel subunits in the female versus male heart [6,[12][13][14]. Estrogen upregulates sarcK ATP channel subunit expression in cardiomyocytes [15], suggesting a potential mechanism for its protective effects in the heart.…”
mentioning
confidence: 99%